Assessment of the chemical profile, polyphenol content and antioxidant activity in extracts of Psidium Guajava L. fruits - Chiari, Bruna Galdorfini [UNESP]; Severi, Juliana Aparecida [UNESP]; De Pauli-Credendio, Priscila Abackerli [UNESP]; Sylos, Célia Maria de [UNESP]; Vilegas, Wagner [UNESP]; Correa, Marcos Antonio [UNESP]; Isaac, Vera Lucia Borges [UNESP] (My University, 2012)
Fruits and vegetables that are rich in polyphenolic compounds, especially flavonoids, may be used to benefit human health by reducing the incidence of cancers and cardiovascular diseases. Previous studies have demonstrated the antioxidant activity of guava, a fruit widely available in Brazil, possibly due to the presence of these polyphenolic compounds. The aim of this study was to analyze the total phenolic and flavonoid contents of various guava extracts, assay their antioxidant activity and record the chromatographic profiles of these extracts, to determine a simple and low way of extracting these compounds efficiently from guava. The results confirmed the presence of polyphenols in guava, including flavonoids, and its antioxidant activity. Furthermore, it was demonstrated that the 70% ethanol (by volume) was the most effective solvent to extract these compounds from the fruit, among those tested.
Keywords: Antioxidants; Flavonoids; Guava; Polyphenols; Psidium guajava L; alcohol; flavonoid; guava extract; polyphenol derivative; antioxidant activity; drug isolation; fruit; nonhuman; phytochemistry